Disruption and deniable interventionism: explaining the appeal of covert action and special forces in contemporary British policy - Cormac, Rory (Sage, 2017)
The United Kingdom has long engaged in covert action. It continues to do so today. Owing to the secrecy involved, however, such activity has consistently been excluded from debates about Britain’s global role, foreign and security policy, and military planning: an important lacuna given the controversy, risk, appeal, and frequency of covert action. Examining when, how, and why covert action is used, this article argues that contemporary covert action has emerged from, and is shaped by, a specific context. First, a gap exists between Britain’s perceived global responsibilities and its actual capabilities; policy elites see covert action as able to resolve, or at least conceal, this. Second, intelligence agencies can shape events proactively, especially at the tactical level, whilst flexible preventative operations are deemed well-suited to the range of fluid threats currently faced. Third, existing Whitehall machinery makes covert action viable. However, current covert action is smaller scale and less provocative today than in the early Cold War; it revolves around “disruption” operations. Despite being absent from the accompanying debates, this role was recognised in the 2015 Strategic Defence and Security Review, which placed intelligence actors at the heart of British thinking.